Communality and indyvidualism of ethics: MacIbtyre, Bauman, Bańka - Skudrzyk, Piotr (Folia Philosophica, 2000)
The article contrasts two approaches to ethics. The communal approach emphasises the social origin and functions of the ethical culture (cf. MacIntyre), while the individualist approach underlines the role of an individual as an ethical subject (cf. Bauman, Baňka). The author point to the importance of the dynamics and vitality of the communal ethics. The individualist ethics he perceives as developing the individual’s sensitivity, while, however, isolating him from the social and communal life.